The 1918 Influenza Pandemic and Subsequent Health Outcomes: An Analysis of SIPP Data - Almond, Douglas; Mazumder, Bhashkar (American Economic Review, 2005)
The 1918 Influenza Pandemic and Subsequent Health Outcomes: An Analysis of SIPP Data by Douglas Almond and Bhashkar Mazumder. Published in volume 95, issue 2, pages 258-262 of American Economic Review, May 2005